Pengambilan Keputusan Kepala Sekolah Ditinjau dari Dimensi Jender, Sosiokultural, Psikologis, dan Geografis - Nurul Ulfatin (Universitas Negeri Malang, 2016)
This descriptive study was aimed at mapping decisions made by principals in terms of gender, socio-cultural, psychological, and geographical dimensions. The sample consisted of 100 principals taken randomly from the primary schools in Malang municipality. Data were gathered by a questionnaire and analyzed descriptively. It was concluded that the decisions made by male and female principals, or by urban, suburban and rural principals seemed to be influenced by socio-cultural and psychological factors. In making decisions, the male principals were influenced by cooperation factor as a sociocultural dimension, and by creativity factor as a psychological dimension